2008
DOI: 10.1139/a08-006
|View full text |Cite
|
Sign up to set email alerts
|

Logging impacts on the biogeochemistry of boreal forest soils and nutrient export to aquatic systems: A review

Abstract: Logging disturbances in boreal forest watersheds can alter biogeochemical processes in soils by changing forest composition, plant uptake rates, soil conditions, moisture and temperature regimes, soil microbial activity, and water fluxes. In general, these changes have often led to short-term increases in soil nutrient availability followed by increased mobility and losses by leaching to receiving waters. Among the studies we reviewed, dissolved organic carbon (DOC) exports usually increased after logging, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
265
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 286 publications
(278 citation statements)
references
References 168 publications
(189 reference statements)
12
265
1
Order By: Relevance
“…Possibly clear-cutting increase stream water nutrient concentrations less in northern than in southern Fennoscandia due to slower mineralization rates and lower deposition fluxes (Akselsson et al 2004;Kortelainen et al 2006;Futter et al 2010;Palviainen et al 2014), and in the northern catchments the observed rise in nutrient loading is largely due to the increased runoff (Ahtiainen and Huttunen 1999;Palviainen et al 2014). The increase in total N, NO 3 -N, NH 4 -N and PO 4 -P concentrations after clear-cutting is in accordance with the results from other boreal catchments (Grip 1982;Rosén et al 1996;Lamontagne et al 2000;Kreutzweiser et al 2008). The increases in the concentrations of N fractions in stream water could result from higher deposition loads due to the lack of N retention by tree canopy (Piirainen et al 2002), reduced nutrient uptake by trees and understory vegetation (Palviainen et al 2007), and increased nitrification in litter layer and soil (Paavolainen and Smolander 1998).…”
Section: Specific Concentrationssupporting
confidence: 85%
See 4 more Smart Citations
“…Possibly clear-cutting increase stream water nutrient concentrations less in northern than in southern Fennoscandia due to slower mineralization rates and lower deposition fluxes (Akselsson et al 2004;Kortelainen et al 2006;Futter et al 2010;Palviainen et al 2014), and in the northern catchments the observed rise in nutrient loading is largely due to the increased runoff (Ahtiainen and Huttunen 1999;Palviainen et al 2014). The increase in total N, NO 3 -N, NH 4 -N and PO 4 -P concentrations after clear-cutting is in accordance with the results from other boreal catchments (Grip 1982;Rosén et al 1996;Lamontagne et al 2000;Kreutzweiser et al 2008). The increases in the concentrations of N fractions in stream water could result from higher deposition loads due to the lack of N retention by tree canopy (Piirainen et al 2002), reduced nutrient uptake by trees and understory vegetation (Palviainen et al 2007), and increased nitrification in litter layer and soil (Paavolainen and Smolander 1998).…”
Section: Specific Concentrationssupporting
confidence: 85%
“…The magnitude and duration of the changes in concentrations depend on several factors such as catchment topography, soil properties, site fertility, atmospheric deposition, vegetation recovery, the timing of management practices and weather conditions after clear-cutting (Ahtiainen and Huttunen 1999;Mattsson et al 2003;Gundersen et al 2006;Palviainen et al 2007;Kreutzweiser et al 2008;Löfgren et al 2009;Futter et al 2010;Palviainen et al 2014). In addition to above-mentioned factors, the location of clear-cut area in relation to the stream may cause variability in treatment effects among studies (Kreutzweiser et al 2008;Abdelnour et al 2011). Also the properties of buffer zones may affect responses (Gundersen et al 2010).…”
Section: Specific Concentrationsmentioning
confidence: 99%
See 3 more Smart Citations